2006
DOI: 10.1039/b604542a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous sorting of magnetic cells via on-chip free-flow magnetophoresis

Abstract: The ability to separate living cells is an essential aspect of cell research. Magnetic cell separation methods are among some of the most efficient methods for bulk cell separation. With the development of microfluidic platforms within the biotechnology sector, the design of miniaturised magnetic cell sorters is desirable. Here, we report the continuous sorting of cells loaded with magnetic nanoparticles in a microfluidic magnetic separation device. Cells were passed through a microfluidic chamber and were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
350
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(357 citation statements)
references
References 31 publications
0
350
0
2
Order By: Relevance
“…The separation in the two types of devices were compared and an amplification in the separation of up to 70% was achieved. Numerical [3][4][5][6][7][8][9][10][11][12][13][14] Pinched flow fractionation ͑PFF͒ is a microchip based size separation technique for nanometer to micrometer sized particles relying on a laminar flow sheet. The method was first demonstrated by Yamada et al, 15 where 15 and 30 m polystyrene microspheres were separated.…”
Section: Separation Enhancement In Pinched Flow Fractionationmentioning
confidence: 99%
“…The separation in the two types of devices were compared and an amplification in the separation of up to 70% was achieved. Numerical [3][4][5][6][7][8][9][10][11][12][13][14] Pinched flow fractionation ͑PFF͒ is a microchip based size separation technique for nanometer to micrometer sized particles relying on a laminar flow sheet. The method was first demonstrated by Yamada et al, 15 where 15 and 30 m polystyrene microspheres were separated.…”
Section: Separation Enhancement In Pinched Flow Fractionationmentioning
confidence: 99%
“…One family of nanomaterials favoured with purification strategies is Superparamagnetic Particles, SPPs. These particles allow for the removal of specific analytes from complex sample matrices using nothing more complicated than a hand held magnet 14,[20][21][22][23] and the use of SPPs has become increasingly common. When they are incorporated into fluidic devices they can be used to continuously sort cells and DNA from liquids 24 , and are integrated into a variety of detection platforms 14,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…27 Tsai et al 28 has showed coating of spherical magnetic particles in microfluidics, with magnetic forces applied to move the microparticles from the aqueous to the non-aqueous phase in a co-laminar flow geometry. Upon passage through the co-laminar interface, the microparticles are coated with a thin O(1) lm layer of the aqueous fluid.…”
Section: Introductionmentioning
confidence: 99%